2021
DOI: 10.3389/fimmu.2021.678483
|View full text |Cite
|
Sign up to set email alerts
|

OVX836 Heptameric Nucleoprotein Vaccine Generates Lung Tissue-Resident Memory CD8+ T-Cells for Cross-Protection Against Influenza

Abstract: Tissue-resident memory (TRM) CD8+ T-cells play a crucial role in the protection against influenza infection but remain difficult to elicit using recombinant protein vaccines. OVX836 is a recombinant protein vaccine, obtained by the fusion of the DNA sequence of the influenza A nucleoprotein (NP) to the DNA sequence of the OVX313 heptamerization domain. We previously demonstrated that OVX836 provides broad-spectrum protection against influenza viruses. Here, we show that OVX836 intramuscular (IM) immunization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…Animal studies have demonstrated the ability of OVX836 to elicit humoral and cellular immunity – including tissue-resident and long-lasting CD8+ T-cells in the lungs - as well as protection in mice and ferrets against influenza A and B challenges ( 16 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated the ability of OVX836 to elicit humoral and cellular immunity – including tissue-resident and long-lasting CD8+ T-cells in the lungs - as well as protection in mice and ferrets against influenza A and B challenges ( 16 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…has been shown to induce improved IgG, CD4 + and CD8 + T-cell responses, uptake of NP antigens into dendritic cells, broad protection against H1N1 and H3N2 lethal challenges in mice and can be used with inactivated influenza vaccines to increase protection ( 244 ). OVX836 vaccination also showed strong long-lasting cross-protection against lethal influenza challenges for a minimum of 90 days in mice ( 245 ). Recently, a phase I clinical trial of OVX836 in adults showed no adverse events across administrations or dosage levels.…”
Section: Recombinant Influenza Vaccinesmentioning
confidence: 99%
“… 24 Antigen-specific memory CD8 + T cell immune response can be formed in healthy people that had been infected with influenza. 25 Influenza-specific CD8 + T cells play a key role in broadly cross-reactive immunity to influenza viruses because they recognize peptide fragments of 8–11 amino acids in length that are derived from highly conserved internal viral proteins in the context of MHC class I molecules. 26 Following activation, CD8 + T cells also secrete antiviral cytokines such as IL-2, IFN-γ, and TNF-α, which further recruit innate and adaptive immune cells to the sites of viral dissemination and induce antiviral responses in infected cells.…”
Section: Discussionmentioning
confidence: 99%